(3GdQjGVjGJ aj GdGbJUGO hGdJLGQI hGdYdhe GdGOGQjI (B/s - (3GdGTbQ, GMeOs ((3YeGf(B: s (3GdOGQ GdKbGaI(B, s, 2001)
(3jHMK gPG GdcJGH aj Md GdeYGOdGJ h GdeJQGLMGJ h JWHjbGJgG ceG jJfGhd Md GdeYGOdGJ h GdeJQGLMGJ h GdeUahaGJ h JWHjbGJgG h GdHQeLI GdNWjI h GdeUahaGJ h GdCTYI h GdYedjGJ GdLHQjI Ydi GdeUahaGJ(B. (3h jOQS GdHGH GdKGfj ef GdcJGH GdOGdI aj eJMhd hGMO h JYjjfgG h fgGjJgG h GSJeQGQgG hGTJbGbgG, h GdOGdI aj YOO ef GdeJMhdGJ h JYjjf fgGjJgG GdYXei h GdUZQi h JWHjbGJgG(B. (3Ke jfJbd Edi TQM GdJcGed h bhGYOg h JWHjbGJg GdGbJUGOjI, HGdEVGaI Edi GdeJhGdjGJ GdMSGHjI h GdaGFOI HCfhGYgG(B. (3h jJejR GdcJGH HGSJNOGe GdCSGdjH GdQjGVjI, MjK jMJhj Ydi eLehYI cHjQI ef GdJWHjbGJ GdQjGVjI h GdJeGQjf, h Pdc HCSdhH Sgd NGd ef GdJYbjO h HdZI eHSWI jSJWjY GdbQGA HeNJda eSJhjGJge agegG h GSJjYGHgGs
(3HjHGjhZQGajG U(B.287s
Keywords: (3GdQjGVjGJs; (3GdeJJGdjGJ GdMSGHjIs; (3GdeJQGLMGJs; (3GdeUahaGJs